2012
DOI: 10.4103/1658-354x.101213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding dexamethasone to bupivacaine on transversus abdominis plane block for abdominal hysterectomy: A prospective randomized controlled trial

Abstract: Purpose:Different adjuvants have been used to improve the quality and increase the duration of local anesthetics during various nerve block techniques. The current study was aimed to evaluate the effect of adding dexamethasone to bupivacaine on the quality and duration of transversus abdominis plane (TAP) block.Methods:Sixty adult patients undergoing elective open abdominal hysterectomy were randomly allocated to receive TAP block using 20 mL of bupivacaine hydrochloride 0.25% + 2 mL saline 0.9% (control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 25 publications
7
48
1
Order By: Relevance
“…In agreement with our find a RCT by Sachdeva and Sinha on 70 patients investigated the effect of dexamethasone as additive to Ropivacaine on ultrasound-Guided Transversus abdominis plane block in Cesarean Section, and showed decreased tramadol requirement postoperatively in dexamethasone when compared to the non dexamethasone group (100.00 ± 0.00 vs. 140.00 ± 50.26 mg, P = 0.046) (18) Ammar and mahmoud (17) also studied the effect of adding dexamethasone to bupivacaine on TAP block and showed that the total post operative 24 hr morphine consumption was significantly reduced in dexamethasone group 19.2 ( 8.1-24.2) vs 4.1( 1.7-6.2) p=0.01. This was comparable with our finding when an opioid conversion factor of morphine to tramadol is applied (1:10).…”
Section: Incidence Of Postoperative Complicationssupporting
confidence: 88%
See 1 more Smart Citation
“…In agreement with our find a RCT by Sachdeva and Sinha on 70 patients investigated the effect of dexamethasone as additive to Ropivacaine on ultrasound-Guided Transversus abdominis plane block in Cesarean Section, and showed decreased tramadol requirement postoperatively in dexamethasone when compared to the non dexamethasone group (100.00 ± 0.00 vs. 140.00 ± 50.26 mg, P = 0.046) (18) Ammar and mahmoud (17) also studied the effect of adding dexamethasone to bupivacaine on TAP block and showed that the total post operative 24 hr morphine consumption was significantly reduced in dexamethasone group 19.2 ( 8.1-24.2) vs 4.1( 1.7-6.2) p=0.01. This was comparable with our finding when an opioid conversion factor of morphine to tramadol is applied (1:10).…”
Section: Incidence Of Postoperative Complicationssupporting
confidence: 88%
“…This can be due to difference in surgical procedure, design and follow up interval. Furthermore, another study in Egypt showed addition of dexamethasone to bupivacaine for transversus abdominis plane block significantly decreased VAS score at 2hr (4.9 vs. 28.1, P=0.01),4hr (12.2 vs. 31.1, P=0.01) and 12hr (15.7 vs. 25.4, P=0.02) but not at 24 th hr ( p=0.41) (17). This can be due to different dose of bupivacaine (they used 20ml only) and difference in population and study design Our study found a significantly reduced post-operative analgesic consumption (tramadol and Diclofenac) in both dexamethasone groups when compared to the control (TAP alone) group.…”
Section: Incidence Of Postoperative Complicationsmentioning
confidence: 95%
“…Brachial plexus blocks with lidocaine plus epinephrine were prolonged two-fold by the addition of dexamethasone in one recent study of patients undergoing elective hand, forearm, and elbow surgery [ 73 ]. Time to first analgesic request after transversus abdominis plane (TAP) blocks performed with bupivacaine for abdominal hysterectomy were prolonged by approximately one hour by the addition of dexamethasone [ 74 ]. Rasmussen et al recently performed a retrospective review of 1,040 patient records and found that when added to ropivacaine, dexamethasone prolonged a range of upper and lower extremity peripheral nerve blocks by a median of 37% [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 164 initially evaluated abstracts, 20 studies were initially selected ( Figure 1 ). Eleven studies were subsequently excluded: five studies were not randomized trials [ 25 29 ], three studies evaluated systemic dexamethasone [ 30 32 ], two studies did not evaluate peripheral blocks [ 33 , 34 ], and one study did not provide a direct comparison [ 35 ]. The characteristics of included studies are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%